Intraocular Pressure Response to Short-Term Extreme Normobaric Hypoxia Exposure - Najmanová, Eliška; Pluháček, František; Botek, Michal; Krejčí, Jakub; Jarošová, Jana (Frontiers in Endocrinology, 2019)
Purpose: The purpose of the study was to determine the intraocular pressure response to normobaric hypoxia and the consequent recovery under additional well-controlled ambient conditions. Second, the study attempted to determine if the intraocular pressure changes were dependent on its baseline, initial heart rate, sex and arterial oxygen saturation. Methods: Thirty-eight visually healthy volunteers (23 women and 15 men) of an average age 25.2 ± 3.8 years from forty-nine recruited participants met the inclusion criteria and performed the complete test. Initial intraocular pressure (baseline), heart rate, and arterial oxygen saturation were measured after 7 minutes of rest under normal ambient conditions at an altitude 250 m above sea level. Each subject then underwent a 10 minute normobaric hypoxic exposure and a subsequent 7 minute recovery under normoxic conditions. Within hypoxic period, subjects were challenged to breathe hypoxic gas mixture with fraction of inspired oxygen of 9.6% (∼ 6.200 m above sea level). Intraocular pressure and arterial oxygen saturation were re-measured at 4 and 10 minutes during the hypoxia and at 7 minutes after hypoxia termination. Results: Intraocular pressure increased in 1.2 mmHg ± 1.9 mmHg and 0.9 mmHg ± 2.3 mmHg at 4 and 10 minutes during the hypoxic period and returned approximately to the baseline at 7 minutes of recovery. The influence of sex was not statistically significant. The arterial oxygen saturation decreased in 14.9% ± 4.2% at minute 4 and 18.4% ± 5.8% at minute 10 during hypoxia and returned to the resting value at 7 minutes of recovery. The decrease was slightly higher in the case of women if compared with men. The hypoxia induced changes in intraocular pressure were significantly correlated with the arterial oxygen saturation changes, whereas the relationship with intraocular pressure baseline and initial heart rate were insignificant. Conclusion: There was a significant increase in intraocular pressure as a response to short-term normobaric hypoxia, which returned to the baseline in 7 minutes after hypoxia. The increase was dependent on the induced oxygen desaturation.